Blockchain Technology as a Security Media for E-Commerce Transaction Process - Soegoto, Eddy Soeryanto; Elfiyah, E; Adilah, N; Kamil, N H (Universitas Komputer Indonesia, 2024)
The purpose of this study is to design the application of blockchain technology in an e-commerce service. The method used in this research was qualitative descriptive analysis and supported by literature studies. The results show that applying this technology can reduce the potential loss of tax fraud in VAT reporting. Blockchain technology implementation is done to solve fraud, limit contact between purchases and sellers, and misuse personal data by increasing security and transparency by applying cryptocurrency in payments. This technology is also reliable to solve the problems of taxation and improve the efficiency of tax digitization. So it can be concluded that in the future, blockchain technology is one of the security systems for making e-commerce transactions and payment systems that are easier, more efficient, and well-documented so that can reduce fraud in VAT reporting by e-commerce.